The Role of CSR in Enhancing Vocational Education for Community Social Welfare - Soulthoni, Hannin Pradita Nur; Rizki, Dian Puspita; Harnia, Sitti (University of Padjadjaran, 2025)
This study aims to explore the role of Corporate Social Responsibility in enhancing the quality of vocational education through industry-education collaboration, particularly in improving students' digital skills and carCorporate Social Responsibility (CSR) is increasingly promoted as a mechanism to support educational development, yet empirical explanations of how CSR generates educational outcomes in vocational contexts remain limited. This study examines how CSR-driven technology interventions contribute to educational transformation through a qualitative case study of SMK Forward Nusantara Depok, Indonesia. Drawing on Creating Shared Value and Human Capital theories, the study proposes a CSR-Driven Educational Transformation Model to explain the link between CSR inputs and learning outcomes. A theory-informed single-case design was employed, using semi-structured interviews with corporate representatives, school leaders, and students, supported by observation and document analysis. Data were analyzed thematically to examine pathways related to technology access, pedagogical change, digital competency development, and career readiness. The findings show that CSR interventions improved digital infrastructure and enabled more applied, industry-relevant learning practices, contributing to enhanced digital skills and career readiness. However, the study also highlights boundary conditions, including sustainability risks, ethical concerns, and institutional readiness. Overall, this study provides a process-based contribution to CSR and vocational education literature and offers practical insights for designing sustainable CSR-education partnerships.